Thermal comfort in existing terraced houses in Malaysia : energy saving strategies to reduce the use of airconditioners - Ahmad, Supian; Doris Toe, Hooi Chyee (Faculty of Built Environment, 2008)
This study investigates the effectiveness of night ventilation as a passive cooling technique for Malaysian terraced houses in view of reducing air-conditioner usage. Night ventilation has received less attention in hot-humid climate even though it is recognized as an effective low-energy technique to cool well-insulated, high mass structures in various other climates. A field experiment was conducted in two adjacent typical terraced houses to compare the indoor thermal environment in night ventilated condition with daytime ventilation, full-day ventilation and no ventilation conditions respectively. Measurement results of the indoor thermal environment reveal that night ventilation provides better diurnal and nocturnal air temperature reductions compared to the other ventilation conditions. However, nocturnal minimum air temperatures in night ventilated condition are still about 2.0oC higher than the ambient air. It was discovered that indoor relative humidity reached 65-70% during daytime and 80-85% during night-time when night ventilation is applied. Further analysis on the vertical distribution of indoor temperatures shows that diurnal maximum air temperatures on the first floor are 1.5-2.0oC higher than those of the ground floor on typical fair weather days. It was found that the uninsulated roof and ceiling might be the main cause for the higher temperature on the first floor. Despite these constraints, night ventilation improves indoor thermal comfort more than the other ventilation conditions based on operative temperature index. It fulfills the Adaptive Comfort Standard well, except on the afternoon of typical fair weather days. It was also found that ceiling fans is effective in lowering SET* further, but not air temperature. It is possible to apply the night ventilation technique for Malaysian terraced houses but the present setbacks need to be addressed for more effective cooling.